Impact of head models in N170 component source imaging: results in control subjects and ADHD patients - Beltrachini, Leandro (2011)
The major goal of evoked related potential studies arise in source localization techniques to identify the loci of neural activity that give rise to a particular voltage distribution measured on the surface of the scalp. In this paper we evaluate the effect of the head model adopted in order to estimate the N170 component source in attention deficit hyperactivity disorder (ADHD) patients and control subjects, considering faces and words stimuli. The standardized low resolution brain electromagnetic tomography algorithm (sLORETA) is used to compare between the three shell spherical head model and a fully realistic model based on the ICBM-152 atlas. We compare their variance on source estimation and analyze the impact on the N170 source localization. Results show that the often used three shell spherical model may lead to erroneous solutions, specially on ADHD patients, so its use is not recommended. Our results also suggest that N170 sources are mainly located in the right occipital fusiform gyrus for faces stimuli and in the left occipital fusiform gyrus for words stimuli, for both control subjects and ADHD patients. We also found a notable decrease on the N170 estimated source amplitude on ADHD patients, resulting in a plausible marker of the disease.